Cyclic compressive loading on 3D tissue of human synovial fibroblasts upregulates prostaglandin E2 via COX-2 production without IL-1β and TNF-α. Issue 9 (September 2014) - Shimomura, K.; Kanamoto, T.; Kita, K.; Akamine, Y.; Nakamura, N.; Mae, T.; Yoshikawa, H.; Nakata, K.
Abstract : Objective: Excessive mechanical stress on synovial joints causes osteoarthritis (OA) and results in the production of prostaglandin E2 (PGE2), a key molecule in arthritis, by synovial fibroblasts. However, the relationship between arthritis-related molecules and mechanical stress is still unclear. The purpose of this study was to examine the synovial fibroblast response to cyclic mechanical stress using an in vitro osteoarthritis model. Method: Human synovial fibroblasts were cultured on collagen scaffolds to produce three-dimensional constructs. A cyclic compressive loading of 40 kPa at 0.5 Hz was applied to the constructs, with or without the administration of a cyclooxygenase-2 (COX-2) selective inhibitor or dexamethasone, and then the concentrations of PGE2, interleukin-1β (IL-1β), tumour necrosis factor-α (TNF-α), IL-6, IL-8 and COX-2 were measured. Results: The concentrations of PGE2, IL-6 and IL-8 in the loaded samples were significantly higher than those of unloaded samples; however, the concentrations of IL-1β and TNF-α were the same as the unloaded samples. After the administration of a COX-2 selective inhibitor, the increased concentration of PGE2 by cyclic compressive loading was impeded, but the concentrations of IL-6 and IL-8 remained high. With dexamethasone, upregulation of PGE2, IL-6 and IL-8 was suppressed. Conclusion: These results could be useful in revealing the molecular mechanism of mechanical stress in vivo for a better understanding of the pathology and therapy of OA. Cite this article: Bone Joint Res 2014;3:280–8.